Study of a new wave energy converter with perturb and observe maximum power point tracking method - Guarniz Avalos, Gustavo Omar (2023)
Ocean waves contain the highest energy density among renewable energy sources. However, harnessing the energy from ocean waves represents a challenge because wave energy converters (WECs) must be designed to have great survivability and efficiency. The power production challenge of any WEC depends on the power take-off (PTO) system efficiency. Maximum power point tracking (MPPT) algorithms have been widely applied in renewable energy from photovoltaic and wind sources, and have subsequently been adapted to wave energy converters (WECs). Energy extraction is optimized by applying MPPT, resulting in an increase in efficiency. This study aims to address the analysis of the influence of the perturb and observe MPPT in the electrical power performance of a WEC composed of a point absorber, a hinged arm and a direct mechanical drive PTO system. The PTO is characterized by a pulley system, a counterweight, one-way bearings, a gearbox, a flywheel and an electric generator; in the present study it is considered to be a cylindrical point absorber. The linear theory and the viscous damping effect are applied to analyze the hydrodynamic behavior of the point absorber. Regarding the two generators considered in the present study, the contribution of MPPT is greater for the low power generator; the high values of the capture width ratio (CWR) occur at low values of period and wave height, showing the maximum value in the high-power generator.